Patient safety in medical education: Tunisian students' attitudes. Issue 1 (31st December 2022) - Ezzi, Olfa; Mahjoub, Mohamed; Omri, Nihel; Ammar, Asma; Loghmari, Dorra; Chelly, Souhir; Mtira, Abir; Rhimi, Sana; Njah, Mansour
ABSTRACT: Health care delivery continues to be unsafe despite major patient safety (PS) improvement efforts over the past decade. Medical school education plays an important role in promoting this culture during initial training. To determine undergraduate medical students' attitudes toward PS at a Tunisian medical school. We carried out a cross-sectional study among undergraduate medical students at Ibn Al Jazzar Medical School in Sousse, Tunisia, using a self-administered questionnaire inspired from the valid tool: Attitudes to Patient Safety Questionnaire (APSQ III). A total of 178 medical students responded to the questionnaire. Medical students tend to have an overall positive perceptions of PS culture with a global mean score 5.33 ± 0.5. Among the individual domains 'Working hours as a cause of error' earned the highest score (6.38 ± 1.0) followed in order by 'Team functioning' (6.24 ± 0.8), 'Error inevitability' (5.91 ± 1.0) and 'Patient involvement in reducing error' (5.50 ± 1.0). The lowest score was for 'Professional incompetence as a cause of error' (4.01 ± 1.0). A PS domain's mean scores comparison based on socio-demographic variables: gender, age, academic year and on PS training revealed a statistically significant difference (p < 0.05) for five PS key dimensions: ' Error reporting confidence ', ' Working hours as a cause of error ', ' Professional incompetence as a cause of error ', ' Team functioning ' and 'PS training received'. Tunisian medical students showed positive attitude towards PS. Nevermore, intensive in terms of frequency and duration sessions, based on various teaching methods may be needed to fulfill students' educational needs.